Analisis Sensitivitas dalam Optimalisasi Keuntungan Produksi Busana dengan Metode Simpleks - A.A.Sri Desiana Shintya Dewi; Ni Ketut Tari Tastrawati; Kartika Sari (Jurnal Matematika, 2014)
The main goal of every company in business is the optimal profit. Challenges that often faced by companies in achieving maximum profit is the difficulty of combining every available resources of the company. The purpose of this study was to determine the maximum profit that can be obtained by Ls Garment using the simplex method and determine the impact of the changes that occur in the objective function coefficients and constants right side constraints to the optimal solution. Based on the results of the application method used, it was obtained maximum profit of Rp. 1.893.184,00 per day with the amount of Dress Payung, Celana Aladdin XL, Celana Aladdin XXL, Celana Aladdin ¾, Dress Kerut, and Daster Haji respectively are 34, 60, 68, 96, 26, and 26 pieces. Profit remain in optimal condition if the change of coefficients value at the objective function is less than or equal to the coefficient of the objective function at the initial model.